Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X di SMA Swasta Bukambero pada Materi Sistem Persamaan Linear Dua Variabel dengan Model Pembelajaran Problem Based Learning - Tena, Yohanes Fridolin; Making, Samuel R. M.; Lede, Yulius K.; Lubur, Dorothea Novia Ludo (Indo-MathEdu Intellectuals Journal, 2025)
This study focuses on improving the critical thinking skills of tenth-grade students at SMA Swata Bukambero on the subject of two-variable linear equation systems using the problem-based learning model. This study used the Classroom Action Research method, involving 30 students from class XA as research subjects. The object of this study was to improve students' critical thinking skills in solving problems on SPLDV. This study was conducted in two cycles with the stages of planning, implementation, observation, and reflection. Data were collected through observation sheets and test questions, then analyzed qualitatively and quantitatively. The results of the analysis showed positive changes, including an increase in student enthusiasm in participating in the lesson. Based on the average value of the concept understanding test in cycles I and II, the number of students who completed the first cycle was 13 students with a classical completion percentage of 43.4%, while in cycle II there were 25 students who completed the classical completion percentage of 83.4%. From the above results, it can be concluded that the problem-based learning model can improve students' critical thinking skills on the subject of two-variable linear equation systems.